Soils in the memory of world nations - Гавриш, Наталія Степанівна; Гавриш, Н.С.; Гавриш, Наталия Степановна; Havrysh, Natalia S.; Позняк, Степан Павлович; Позняк, С. П.; Pozniak, Stepan P. (Maria Curie-Skłodowska University in Lublin, 2019)
The most important feature of the primary accumulation of different facts about the properties of soils, their fertility and ways of cultivation is the human awareness of soil as the environment of growth and development of plants, as well as the existence of a large variety of soils and the need for their differentiated use in the agriculture and different taxation systems. Monuments are important in the case of careful treatment and conservation of natural objects, including soils. Monuments to soils have been preserved in ancient writings – Egyptian papyri and steles, chronicles, maps, etc. Taking into account the importance of chernozem for nature and for humans as well, a number of monuments, scientifi works, fition, or poems are devoted to this particular type of soil. There are also announced “years of chernozem”, indicating it as the standard of excellence in the world soils. Analysis of the development of soil science has shown that it has a long history, from ancient times to the present day. The main idea is that soil plays an important role both for nature and humanity. An important task of modern society is a reasonable approach towards the soil and preservation of natural soil objects.
Pozniak S. P. Soils in the memory of world nations / S. Pozniak, N. Havrysh // Polish Journal of Soil Science. - Maria Curie-Skłodowska University in Lublin, 2019. - Vol. 52. - Issue 1. - P. 13-22.
Keywords: soil; chernozem; natural monuments; ґрунти; чорноземи; пам’ятки природи; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING